Identifying optimal PD-1/PD-L1 inhibitors in first-line treatment of patients with advanced squamous non-small cell lung cancer in China: Updated systematic review and network meta-analysis - Mingye Zhao; Mingye Zhao; Taihang Shao; Taihang Shao; Yinan Ren; Yinan Ren; Caicun Zhou; Wenxi Tang; Wenxi Tang (Frontiers Media S.A., 2022)
Objective: After Gemstone-302 was published in Lancet in January 2022, seven PD-(L)1 inhibitors launched or about to be launched in China, but there are no head-to-head RCTs reporting the comparative efficacy for squamous non-small cell lung cancer (sq-NSCLC). Therefore, we aimed to indirectly compare the efficacy of these treatments to provide evidence for clinical decision and Chinese national reimbursement drug listing.Methods: We collected phase III clinical trials targeted on stage IIIB-IV patients for first-line immunotherapy of sq-NSCLC by systematically searching databases. Relative effects of competing treatments were assessed by Bayesian network meta-analysis and non-parametric restricted mean survival time (RMST) model. Hazard ratio (HR), severe adverse events (SAEs, grade 3-5), progression-free survival (PFS) and overall survival (OS) years were the outcomes. Subgroup analysis was done according to PD-(L)1 expression, smoking, gender, Eastern Cooperative Oncology Group performance status, age and disease stage. Sensitivity analysis using the range of parameters distribution as well as different comparison methods was performed to test the robustness of the results.Results: A total of 7 clinical trials with 2,640 patients were included. For OS, the efficiency (HR, 95%CI) ranks from high to low were sugemalimab (0.48, 0.32-0.73), camrelizumab (0.55, 0.40-0.76), sintilimab (0.56, 0.35-0.90), pembrolizumab (0.71, 0.58-0.87) and atezolizumab (0.88, 0.73-1.05). For PFS, the efficiency ranks from high to low were sugemalimab (0.33, 0.24-0.45), camrelizumab (0.37, 0.30-0.46), tislelizumab (0.53, 0.36-0.79), sintilimab (0.54, 0.42-0.69), toripalimab (0.56, 0.38-0.83), pembrolizumab (0.57, 0.47-0.70) and atezolizumab (0.71, 0.59-0.85). Proportional hazard models and non-proportional hazard models showed consistent efficiency ranks. When extrapolated to long-term survival benefit, under non-proportional hazard ratio, sugemalimab achieved the highest PFS benefit (lifeyears, LYs) in 2 years (1.323), with camrelizumab (1.320), sintilimab (1.243), tislelizumab (1.189), pembrolizumab (0.990) and atezolizumab (0.947) ranking in order; Camrelizumab achieved the highest OS benefit (LYs) in 10 years (2.723), with atezolizumab (2.445) and pembrolizumab (2.397) ranking in order. RMST model showed similar results. In terms of safety, PD-(L)1 inhibitors increased the incidence of SAEs when combined with chemotherapy, sugemalimab and camrelizumab was the safest drugs.Conclusion: Sugemalimab is superior both in HR and long-term survival benefit for Chinese patients with advanced sq-NSCLC.